(untitled) (Jurnal Bahasa, 2021)
The alternation of one segment to another is a common phenomenon that occurs in dialects or languages. However, the alternation of a segment to several other segments is an uncommon phonological phenomenon that only few studies have discussed. This current study thus aims to identify the phonological phenomenon of the mid-vowel schwa in the Minangkabau language in Peninsular Malaysia that alternates to other segments, and to explain each of those phonological phenomena using the analysis of features of Chomsky and Halle’s Transformational-generative theory (1968). Minangkabau language data was obtained from previous studies conducted by Asmah et al. (2013) and Ernawati (2019), which were gathered from Kampung Sesapan Batu Minangkabau in Beranang. A total of 219 words that exhibit the behaviours of the schwa were taken for analysis purposes, that is 211 words from Asmah et al. (2013) and eight words from Ernawati (2019). The findings show that there are four phonological behaviours of schwa in the Minangkabau language namely, (1) alternation of schwa to [a], (2) alternation of schwa to [ɔ], (3) retention of schwa in the output, and (4) deletion of schwa and the following segment. Keywords: Schwa, Minangkabau dialect, phonology, distinctive feature, Transformational-generative theory Link: PDF